2017
DOI: 10.1055/s-0043-119213
|View full text |Cite
|
Sign up to set email alerts
|

Impact of preprocedure simethicone on adenoma detection rate during colonoscopy: a multicenter, endoscopist-blinded randomized controlled trial

Abstract: Combined use of PEG and simethicone is associated with a significantly increased ADR in a Chinese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(98 citation statements)
references
References 34 publications
8
88
2
Order By: Relevance
“…The result of meta‐analysis of ADR is in accordance with results of studies conducted by Bai et al . and Zhang et al ,.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The result of meta‐analysis of ADR is in accordance with results of studies conducted by Bai et al . and Zhang et al ,.…”
Section: Discussionsupporting
confidence: 89%
“…Better bowel preparation makes it possible to find smaller adenomas. Bai et al . reported 94 adenomas (size ≤ 5 mm) in the SIM group versus 40 in the non‐SIM group, Pontone et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search strategy identified 535 potentially relevant records after excluding duplicates. After careful review, 36 studies that met inclusion criteria were further evaluated for eligibility, and 12 full‐text articles from 2009 to 2017 were included in this meta‐analysis . The review process is illustrated by a flowchart of Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…One meta‐analysis showed that oral simethicone helps reduce bubbles and improves visibility in upper gastrointestinal endoscopy, but the ADR was not evaluated because few studies had addressed this issue at the time it was published. Several subsequent randomized controlled trials evaluated the bowel cleansing effects of adjuvant simethicone; however, whether it had a beneficial role in ADR or polyp detection rate (PDR) had yet to be confirmed …”
Section: Introductionmentioning
confidence: 99%